Maternal betaine suppresses adrenal expression of cholesterol trafficking genes and decreases plasma corticosterone concentration in offspring pullets - Abobaker, Halima (J Anim Sci Biotechnol, 2019)
BACKGROUND: Laying hens supplemented with betaine demonstrate activated adrenal steroidogenesis and deposit higher corticosterone (CORT) in the egg yolk. Here we further investigate the effect of maternal betaine on the plasma CORT concentration and adrenal expression of steroidogenic genes in offspring pullets. RESULTS: Maternal betaine significantly reduced (P < 0.05) plasma CORT concentration and the adrenal expression of vimentin that is involved in trafficking cholesterol to the mitochondria for utilization in offspring pullets. Concurrently, voltage-dependent anion channel 1 and steroidogenic acute regulatory protein, the two mitochondrial proteins involved in cholesterol influx, were both down-regulated at mRNA and protein levels. However, enzymes responsible for steroid syntheses, such as cytochrome P450 family 11 subfamily A member 1 and cytochrome P450 family 21 subfamily A member 2, were significantly (P < 0.05) up-regulated at mRNA or protein levels in the adrenal gland of pullets derived from betaine-supplemented hens. Furthermore, expression of transcription factors, such as steroidogenic factor-1, sterol regulatory element-binding protein 1 and cAMP response element-binding protein, was significantly (P < 0.05) enhanced, together with their downstream target genes, such as 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase, LDL receptor and sterol regulatory element-binding protein cleavage-activating protein. The promoter regions of most steroidogenic genes were significantly (P < 0.05) hypomethylated, although methyl transfer enzymes, such as AHCYL, GNMT1 and BHMT were up-regulated. CONCLUSIONS: These results indicate that the reduced plasma CORT in betaine-supplemented offspring pullets is linked to suppressed cholesterol trafficking into the mitochondria, despite the activation of cholesterol and corticosteroid synthetic genes associated with promoter hypomethylation.